Common polygenic variation in the early medication change (EMC) cohort affects disorder risk, but not the antidepressant treatment response - Müller, Svenja; Lieb, Klaus; Streit, Fabian; Awasthi, Swapnil; Wagner, Stefanie; Frank, Josef; Müller, Marianne B.; Tadic, André; Heilmann-Heimbach, Stefanie; Hoffmann, Per; Mavarani, Laven; Schmidt, Börge; et al. (Journal of affective disorders, 2024)
Background - Given the great interest in identifying reliable predictors of the response to antidepressant drugs, the present study investigated whether polygenic scores (PGS) for Major Depressive Disorder (MDD) and antidepressant treatment response (ADR) were related to the complex trait of antidepressant response in the Early Medication Change (EMC) cohort. - Methods - In this secondary analysis of the EMC trial (N = 889), 481 MDD patients were included and compared to controls from a population-based cohort. Patients were treated over eight weeks within a pre-defined treatment-algorithm. We investigated patients' genetic variation associated with MDD and ADR, using PGS and examined the association of PGS with treatment outcomes (early improvement, response, remission). Additionally, the influence of two cytochrome P450 drug-metabolizing enzymes (CYP2C19, CYP2D6) was determined. - Results - PGS for MDD was significantly associated with disorder status (NkR2 = 2.48 %, p < 1*10−12), with higher genetic burden in EMC patients compared to controls. The PGS for ADR did not explain remission status. The PGS for MDD and ADR were also not associated with treatment outcomes. In addition, there were no effects of common CYP450 gene variants on ADR. - Limitations - The study was limited by variability in the outcome parameters due to differences in treatment and insufficient sample size in the used ADR genome-wide association study (GWAS). - Conclusions - The present study confirms a polygenic contribution to MDD burden in the EMC patients. Larger GWAS with homogeneity in antidepressant treatments are needed to explore the genetic variation associated with ADR and realize the potential of PGS to contribute to specific response subtypes.
Online verfügbar: 20. Juli 2024, Artikelversion: 1. August 2024
Gesehen am 20.11.2024